Menyoal Keberimbangan dan Akurasi Berita Dalam Segmen Hard News RRI Pro-3 Periode Siar Mei-Juli 2021 - Ade Irma Sukmawati; Puji Rianto; Al Musa Karim (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
RRI Pro-3 as a public broadcasting institution taking the task on conveying information in a neutral, independent, as well as non-commercial ways. With the purpose of monitoring the quality of RRI Pro-3 news content, then research on news content analysis was conducted. Research on news content analysis was carried out on the hard news segment of RRI Pro-3 which was broadcast at 07.00, 13.00 and 19.00. The stages of analysis in this news content analysis research were inter-coder reliability test, measuring instrument reliability test, data selection, data initial test, description of descriptive data processing, mean data processing, correlation test, and data validity test. The results of content analysis research on the reliability test between coders show a value of 96.29%, the reliability test of the measuring instrument is 0.834 with an alpha of 5%. The description of descriptive data processing gives results in the form of information on the distribution of aspects that become supporting information for the news. Mean data processing was obtained by measuring the average aspects of accuracy, balance and neutrality. Correlation test was conducted between news themes and aspects of accuracy, balance and neutrality. The data validity test was carried out to determine the validity of the processed data, the validity value was obtained at an accuracy of 0.868**, a balance of 0.680**, a neutrality of 0.2533** (negative question). The research results provide information that the quality of the RRI Pro-3 news is good, aspects that can be improved is the balance of information through the presence of expert resource persons. It can be concluded that the existence of expert resourcepersons as part of the balance of information will not only facilitate public understanding of listeners but also educate the listeners.